Size composition, reproductive biology, age and growth of largehead cutlassfish Trichiurus lepturus Linnaeus from the Arabian Sea coast of Oman - Al-Nahdi, A; Al Marzouqi, A; Al-Rasadi, E; Groeneveld, J C (Indian Journal of Fisheries, 2011)
Largehead cutlassfish caught by traditional and commercial fishers along the Arabian Sea coast of Oman between January 2001 and December 2002 were studied to determine size composition, size at first maturity (L50), reproductive season, age and growth. The total length (TL) of cutlassfishes sampled ranged from 16 to 126 cm and the average size of specimens caught by trawlers (92.6 Â± 15.3 cm) was smaller than those caught by traditional fishers (98.8 Â± 10.4 cm), suggesting gear selectivity. Females dominated samples (1F:0.12M), matured at an average TL of 79 cm and females with ripe ovaries occurred almost throughout the year. The gonado-somatic index of females (GSI) peaked in May and declined sharply in June and a spawning season at the onset of the SW monsoon winds is also supported by the hepato-somatic index (HSI) and condition index (CI) trends. The length-weight relationship was TW=3Ã—10-4TL3.3155 and the conversion factor from TL to preanal length was 0.55. Growth rings were counted on the otoliths of 378 cutlassfish and an age-length relationship was estimated with von Bertalanffy growth (VBG) parameters of Lâˆ (127.4cm TL), K (0.399 yr-1) and t0 (-0.9815 yr). Length frequency data analyzed with ELEFAN software estimated the VBG parameters of Lâˆ, K and t0 as 129cm, 0.459 yr-1 and - 0.69 yr respectively